THU0160 THE EFFECT OF HLA-DRB1 RISK ALLELES ON THE CLINICAL EFFICACY AND SAFETY OF ABATACEPT IN SEROPOSITIVE, BIOLOGIC-NAÏVE PATIENTS WITH EARLY, MODERATE-TO-SEVERE RA TREATED WITH ABATACEPT OR ADALIMUMAB: DATA FROM THE OPEN-LABEL SWITCH PERIOD OF THE HEAD-TO-HEAD SINGLE-BLINDED 'EARLY AMPLE' TRIAL. (2nd June 2020) - Rigby, W.; Buckner, J.; Bridges, Jr., S. L.; Nys, M.; Gao, S.; Polinsky, M.; Ray, N.; Bykerk, V.
Abstract : Background: Mechanistic differences between protein biologics are poorly understood. HLA-DRB1 alleles containing the shared epitope (SE), which are strongly associated with RA, are present in 70–80% of anti-citrullinated protein antibody+ patients (pts) with RA. 1 Numerically higher efficacy responses with abatacept (ABA) vs adalimumab (ADA) were reported after 24 wks of treatment (Tx) in pts with early seropositive RA, specifically in SE+ pts. 2 Objectives: To prospectively explore the relationship between HLA-DRB1 SE genotype and the effects on disease activity after switching from ADA to ABA after completing 24 wks of initial Tx in biologic-naïve pts with early active RA. Methods: This head-to-head exploratory trial (NCT02557100 ) enrolled seropositive (anti-cyclic citrullinated peptide 2+ and RF+) adults with early (≤12 mos of symptoms), moderate-to-severe RA (ACR/EULAR 2010 criteria). Pts were randomised 1:1 to SC ABA 125 mg/wk or SC ADA 40 mg every 2 wks (both with stable, oral MTX wkly) for 24 wks (single-blind period). At Wk 28, ADA-treated pts were switched to open-label (OL) ABA, following a 6-wk washout period (switch arm); ABA-treated pts continued treatment with ABA in an OL manner (non-switch arm). Pts were grouped by SE status based on HLA-DRB1 genotype (−, no SE allele; +, ≥1 SE allele). Clinical efficacy was assessed to Wk 48 to determine the proportion of ACR20/50/70 responders and DAS28 (CRP) remitters in each arm. Safety was analysed throughout the trial and up to 8 wks post last dose. Results: All 40 ABA-treated and 36/40 ADA-treated pts entered the OL ABA period; 3 (lost to follow up n=2, other n=1) and 1 (pt request to discontinue) pts, respectively, discontinued during the OL period. Baseline characteristics were balanced 2 ; mean (SD) RA duration was 5.5 (2.6) mos. The greater efficacy responses seen with ABA vs ADA to Wk 24 2 were sustained at Wk 48 in the non-switch arm; in the switch arm, the efficacy responses generally increased over the OL period to Wk 48. Specifically, in both the overall population (Figure 1 ) and among SE+ pts (Figure 2 ), ACR20/50 response rates (RRs) and DAS28 (CRP) remission rates were similar between arms at Wk 48; ACR70 RR was still somewhat higher in the non-switch arm. Among SE− pts, ACR50 RRs were 56% in the non-switch arm vs 44% in the switch arm at Wk 24; at Wk 48, 56% of pts in the non-switch arm and 67% of pts in the switch arm achieved ACR50. However, data from the SE− subgroup must be interpreted with caution due to low pt numbers (n=9/arm). No new safety signals were identified. Conclusion: In this seropositive early RA population, particularly in the SE+ subgroup, a trend towards numerically higher and sustained efficacy responses by stringent definitions was seen in the abatacept non-switch arm at Wk 48; trends towards further improvement were observed in the adalimumab-to-abatacept switch arm. References: [1]Terao C, et al. Arthritis Rheumatol 2015;67 :1744–50. [2]Rigby W, et al. Ann Rheum Dis 2019:78 :abstract 263. Acknowledgments: Marianne Peluso (protocol manager); medical writing: Lola Parfitt (Caudex; funding: BMS) Disclosure of Interests: William Rigby Grant/research support from: Bristol-Myers Squibb, Consultant of: AbbVie, Bristol-Myers Squibb, Genentech, Pfizer, Jane Buckner Grant/research support from: Bristol-Myers Squibb, Janssen, S. Louis Bridges, Jr.: None declared, Marleen Nys Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Sheng Gao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Martin Polinsky Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Neelanjana Ray Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Vivian Bykerk: None declared